2020
DOI: 10.1111/psyp.13696
|View full text |Cite
|
Sign up to set email alerts
|

Chinese characters are read using not only visual but also writing motor information

Abstract: For example, the left or right premotor cortex, which is related to writing-specific processes involving the generation of graphemic motor commands (Beeson et al., 2010), can be engaged in passively viewing or reading real letters, but not pseudo-letters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Second, the overall analysis showed a substantial amount of heterogeneity between-studies, suggesting that the adoption of the diverse methodological parameters might likely explain some of the observed discrepant results. More important, such heterogeneity allowed testing the predictions about the operation of the underlying cognitive mechanism formulated by two proposals: the sensorimotor hypothesis framed by embodied cognition (Bara et al, 2004;Labat et al, 2020;Longcamp et al, 2008;Longcamp et al, 2006;Longcamp et al, 2005;Yin & Zhang, 2021) and the symbolic accounts of the visual analysis and the perceptual variability hypotheses (Courrieu & de Falco, 1989;James & Engelhardt, 2012;Li & James, 2016;Seyll et al, 2020;Williams, 1975). To this aim, we examined four types of moderators: training program (type of control training; presence/absence of phonological training; HW tasks adopted); set size and training regime (amount of training, duration and frequency of sessions); perceptual learning tasks adopted and granularity of visual discrimination; and age of learners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the overall analysis showed a substantial amount of heterogeneity between-studies, suggesting that the adoption of the diverse methodological parameters might likely explain some of the observed discrepant results. More important, such heterogeneity allowed testing the predictions about the operation of the underlying cognitive mechanism formulated by two proposals: the sensorimotor hypothesis framed by embodied cognition (Bara et al, 2004;Labat et al, 2020;Longcamp et al, 2008;Longcamp et al, 2006;Longcamp et al, 2005;Yin & Zhang, 2021) and the symbolic accounts of the visual analysis and the perceptual variability hypotheses (Courrieu & de Falco, 1989;James & Engelhardt, 2012;Li & James, 2016;Seyll et al, 2020;Williams, 1975). To this aim, we examined four types of moderators: training program (type of control training; presence/absence of phonological training; HW tasks adopted); set size and training regime (amount of training, duration and frequency of sessions); perceptual learning tasks adopted and granularity of visual discrimination; and age of learners.…”
Section: Discussionmentioning
confidence: 99%
“…The sensorimotor hypothesis (e.g., Longcamp et al, 2005Longcamp et al, , 2006Longcamp et al, , 2008Yin & Zhang, 2021) is framed by the proposal of embodied cognition (also called grounded or situated cognition: e.g., Allport, 1985;Barsalou, 2008Barsalou, , 2016Kiefer & Pulvermuller, 2012; for a critical discussion, see, e.g., Goldinger, Papesh, Barnhart, Hansen, & Hout, 2016;Machery, 2016;Mahon, 2015;Mahon & Hickok, 2016), which holds that the content and the format of cognitive representations are isomorphic: sensory concepts have a sensorial format and action concepts have a motor format.…”
Section: The Sensorimotor Hypothesis and Embodied Cognitionmentioning
confidence: 99%
“…Second, the overall analysis showed a substantial amount of heterogeneity between-studies, suggesting that the adoption of the diverse methodological parameters might likely explain some of the observed discrepant results. More important, such heterogeneity allowed testing the predictions about the operation of the underlying cognitive mechanism formulated by two proposals: the sensorimotor hypothesis framed by embodied cognition (Bara et al, 2004;Labat et al, 2020;Longcamp et al, 2008;Longcamp et al, 2006;Longcamp et al, 2005;Yin & Zhang, 2021) and the symbolic accounts of the visual analysis and the perceptual variability hypotheses (Courrieu & de Falco, 1989;James & Engelhardt, 2012;Li & James, 2016;Seyll et al, 2020;Williams, 1975) The present meta-analysis showed that the benefit from HW training (over control training) was reliable across different outcomes of perceptual learning, but, more important, this effect was larger when fine-grained than coarse-grained discrimination of graphs was involved. Note that, albeit relevant, this result is compatible with the operation of both sensorimotor and perceptual learning mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The sensorimotor hypothesis (e.g., Longcamp et al, 2005Longcamp et al, , 2006Longcamp et al, , 2008Yin & Zhang, 2021) is framed by the proposal of embodied cognition (also called grounded or situated cognition: e.g., Allport, 1985;Barsalou, 2008Barsalou, , 2016Kiefer & Pulvermuller, 2012; for a critical discussion, see, e.g., Goldinger, Papesh, Barnhart, Hansen, & Hout, 2016;Machery, 2016;Mahon, 2015;Mahon & Hickok, 2016), which holds that the content and the format of cognitive representations are isomorphic: sensory concepts have a sensorial format and action concepts have a motor format.…”
Section: The Sensorimotor Hypothesis and Embodied Cognitionmentioning
confidence: 99%
“…The writing process without visual feedback can modulate orthographic processing when reading Chinese characters (Yin et al, in press). It has been proposed that the processes of learning Chinese might establish a motor gesture decoding system for recognizing Chinese characters (Yin and Zhang, 2021). An empirical study revealed that writing exercises help foreign language learners learn Chinese characters, but stroke order learning may not significantly improve the recognition of Chinese characters (Hsiung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%